Amidation of α-Amino Acids Using Dichloro(methyl)(3,3,3-trifluoropropyl)silane and Imidazole without Conventional Protection and Deprotection of α-Amino Group - Nobuta, Tomoya; Morishita, Honoka; Suto, Yutaka; Yamagiwa, Noriyuki (Synlett, 2022)
Amidation of amino acids using dichloro(methyl)(3,3,3-trifluoropropyl)silane (MTFPSCl2) and imidazole is described. MTFPSCl2 activates the carboxy group and protects the α-amino group of amino acids. The amidation proceeded with 19 amino acids and 19 amines, including α-branched amines and anilines; the corresponding amino acid amides were synthesized in good-to-high yields (up to 96%) with low-to-no racemization.
Keywords: amidation; unprotected amino acid; coupling reagent; silyl reagent; dichloro(methyl)(3,3,3-trifluoropropyl)silane